Ideology and U.S. foreign policy - Hunt, Michael H. (Yale University Press, 1987)
In a major reinterpretation of American diplomatic history, Michael H. Hunt argues that there is an ideology that has shaped American foreign policy--an ideology based on a conception of national mission, on the racial classification of other peoples, and on hostility toward social revolutions--and he traces its rise and impact from the eighteenth century down to the present day. "Michael Hunt effectively analyzes the mental prisms through which perceptions of the American national interest are refracted. Policymakers will find his book provocative. All Americans who care about their country's place in the world will find it worth reading."--Rep. Stephen Solarz "Three 'core ideas' of American political culture, according to Mr. Hunt, have powerfully molded American diplomacy, and they form the heart of his analysis. These ideas concern the questions of revolution, race and, most interestingly, liberty ... On the subject of liberty ... Mr. Hunt is supple and suggestive. ... Mr. Hunt's examination of the conflation of liberty and greatness helps us understand the ideological genesis of the Reagan Doctrine, with is open-ended support for anti-Communist movements everywhere."--David M. Kennedy, New York Times Book Review "A lean, plain-spoken treatment of a grand subject ... A bold piece of criticism and advocacy ... The tight focus of the argument may insure its survival as one of the basic postwar critiques of U.S. policy."--John W. Dower, Bulletin of the Atomic Scientists Michael H. Hunt is professor of history at the University of North Carolina, Chapel Hill.
Keywords: United States -- Foreign relations -- Philosophy.; United States -- Foreign relations.; États-Unis -- Relations extérieures -- Philosophie.; États-Unis -- Relations extérieures.; HISTORY / General.; Diplomatic relations; Diplomatic relations -- Philosophy; United States; Buitenlandse politiek.; Ideologie.; Imperialisme.; Etats-Unis -- relations extérieures -- philosophie.; Geschichte